Diverse migration strategies in hoopoes (Upupa epops) lead to weak spatial but strong temporal connectivity - van Wijk, Rien E; Schaub, Michael; Hahn, Steffen; Juárez-García-Pelayo, Natalia; Schäfer, Björn; Viktora, Lukáš; Martín-Vivaldi, Manuel; Zischewski, Marko; Bauer, Silke (Die Naturwissenschaften, 2018)
The annual cycle of migrating birds is shaped by their seasonal movements between breeding and non-breeding sites. Studying how migratory populations are linked throughout the annual cycle-migratory connectivity, is crucial to understanding the population dynamics of migrating bird species. This requires the consideration not only of spatial scales as has been the main focus to date but also of temporal scales: only when both aspects are taken into account, the degree of migratory connectivity can be properly defined. We investigated the migration behaviour of hoopoes (Upupa epops) from four breeding populations across Europe and characterised migration routes to and from the breeding grounds, location of non-breeding sites and the timing of key migration events. Migration behaviour was found to vary both within and amongst populations, and even though the spatial migratory connectivity amongst the populations was weak, temporal connectivity was strong with differences in timing amongst populations, but consistent timing within populations. The combination of diverse migration routes within populations and co-occurrence on the non-breeding grounds between populations might promote exchange between breeding populations. As a result, it might make hoopoes and other migrating bird species with similar strategies more resilient to future habitat or climatic changes and stabilise population trends.
Keywords: populační dynamika; Europe; Animals; Geolocator; ptáci; Autumn migration; Birds; Spring migration; Population Dynamics; zvířata; Animal Migration; Evropa; Partial migration; migrace zvířat; Wintering